2010
DOI: 10.1016/s0140-6736(10)61303-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral sucrose as an analgesic drug for procedural pain in newborn infants: a randomised controlled trial

Abstract: SummaryBackgroundMany infants admitted to hospital undergo repeated invasive procedures. Oral sucrose is frequently given to relieve procedural pain in neonates on the basis of its effect on behavioural and physiological pain scores. We assessed whether sucrose administration reduces pain-specific brain and spinal cord activity after an acute noxious procedure in newborn infants.MethodsIn this double-blind, randomised controlled trial, 59 newborn infants at University College Hospital (London, UK) were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
230
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(250 citation statements)
references
References 37 publications
7
230
0
6
Order By: Relevance
“…Slater et al 45 found no differences in nociceptive brain activity or in the magnitude or latency of the spinal nociceptive reflexes after the heel stick, between infants who received sucrose and those who received water, although Premature Infant Pain Profile scores and pain-related facial expressions were significantly reduced in the sucrose-treated infants. These findings contradict data from a large body of literature supporting the analgesic efficacy of sucrose or other sweet solutions.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Slater et al 45 found no differences in nociceptive brain activity or in the magnitude or latency of the spinal nociceptive reflexes after the heel stick, between infants who received sucrose and those who received water, although Premature Infant Pain Profile scores and pain-related facial expressions were significantly reduced in the sucrose-treated infants. These findings contradict data from a large body of literature supporting the analgesic efficacy of sucrose or other sweet solutions.…”
Section: Figurementioning
confidence: 98%
“…These findings contradict data from a large body of literature supporting the analgesic efficacy of sucrose or other sweet solutions. Moreover, there are several methodological concerns related to the Slater et al study 45 that make it seem premature to conclude that sucrose is ineffective based only on its findings. 46 Although the differences between the sucrose and combination groups in behavioral and physiologic scores during the recovery phase were statistically significant, the magnitude of these differences is probably not clinically meaningful.…”
Section: Figurementioning
confidence: 99%
“…It has been extensively studied for this purpose, yet many gaps in knowledge remain, including appropriate dosing, mechanism of action, soothing versus analgesic effects, and long-term consequences. [71][72][73] A meta-analysis of 57 studies including >4730 infants with gestational ages ranging from 25 to 44 weeks concluded that sucrose is safe and effective for reducing procedural pain from a single event. 74 Maximum reductions in physiologic and behavioral pain indicators have been noted when sucrose was administered ∼2 minutes before a painful stimulus, and the effects lasted ∼4 minutes.…”
Section: Pharmacologic Treatment Strategies Sucrose and Glucosementioning
confidence: 99%
“…76 In animal studies, the analgesic effects of sucrose appear to be a sweet-taste-mediated response of opiate, endorphin, and possibly dopamine or acetylcholine pathways; however, the mechanism of action is not well understood in human neonates. 72,[77][78][79][80][81] An additive analgesic effect has been noted when sucrose is used in conjunction with other nonpharmacologic measures, such as nonnutritive sucking and swaddling, especially for procedures such as ophthalmologic examinations and immunizations. 74,78 Although the evidence that oral sucrose alleviates procedurally related pain and stress, as judged by clinical pain scores, appears to be strong, a small RCT found no difference in either nociceptive brain activity on electroencephalography or spinal nociceptive reflex withdrawal on electromyography between sucrose or sterile water administered to term infants before a heel lance.…”
Section: Pharmacologic Treatment Strategies Sucrose and Glucosementioning
confidence: 99%
“…Although using sucrose use is safe, [19][20][21][22][23] it does not prevent later exaggerated pain response, 24,25 and its mechanism of action is not fully understood. 26,27 Finally, the evidence is inconclusive on whether multiple doses of sucrose may alter later development. Preterm infants (,31 weeks' estimated gestational age) who received sucrose for all painful procedures during their first 7 days had lower neurodevelopmental scores at term, 18 particularly if they received .10 doses per day.…”
mentioning
confidence: 99%